Detecting Adolescent Students' Mental Health Problems at a School in Ambon City, Indonesia - Lidya Bethsi Evangeline Saptenno (Nusantara Science and Technology Proceedings, 2023)
Globally, the primary disease burden for adolescents today is mental health conditions, which are still often not taken seriously. Many adolescents spend time at school, making it an ideal place to prevent mental health problems. Thus, this research was conducted to detect early adolescent mental health problems at a school in Ambon City. This mixed method study detected mental health problems of adolescent students using the Pediatric Symptom Checklist-17 (PSC-17) questionnaire on 300 respondents. In addition, in-depth interviews were conducted with four informants from the education and health sectors. Forty-one percent (95 girls and 28 boys) of the respondents had a total PSC-17 score ? 15, 57.7% (135 girls and 38 boys) had an internal score ?5, 21.3% (49 girls and 15 boys) had an attention score ? 7 and 9.7% (13 girls and 16 boys) had an externalization score ? 7. This indicates a risk of problems with overall psychosocial functioning with difficulties associated with mostly the internalization subscale and more problems in adolescent girls except for the externalization subscale. With p<0.05, it shows a significant relationship between almost all scores, except internalization scores, with age and grade level. In-depth interviews have shown slightly different opinions about mental health problems in adolescents. Nearly half of the adolescents in this study are at risk of emotional behavior problems, which are often poorly understood and as a result, go unnoticed. This shows how important an early detection strategy is.